2007
DOI: 10.1021/jf062983a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Glucosamine from Exoskeleton of Shrimp and Predicting Production Yield by Response Surface Methodology

Abstract: Chitin was prepared from Persian Gulf shrimp (Metapenaeus monoceros), and then, the obtained chitin was hydrolyzed by hydrochloric acid solutions. The production yield of glucosamine hydrochloride from chitin was optimized, and the effect of three factors (acid concentration, acid to chitin ratio, and reaction time) was investigated. A Box-Behnken design by Minitab software created 12 reactions with different conditions. Each reaction was performed in two replicates. Response surface methodology was used for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 11 publications
0
44
0
7
Order By: Relevance
“…Chitin is a biopolymer composed of N-acetyl-d-glucosamine, which can be found in exoskeletons of invertebrate marine creatures such as oysters, crabs, or shrimps. Glucosamine is usually prepared from chitin by hydrolysis using strong mineral acid (sulphuric or hydrochloric) (Mojarrad et al 2007). During this reaction, chitin is deacetylated and depolymerised to glucosamine salt of the acid used (Figures 1a-c).…”
mentioning
confidence: 99%
“…Chitin is a biopolymer composed of N-acetyl-d-glucosamine, which can be found in exoskeletons of invertebrate marine creatures such as oysters, crabs, or shrimps. Glucosamine is usually prepared from chitin by hydrolysis using strong mineral acid (sulphuric or hydrochloric) (Mojarrad et al 2007). During this reaction, chitin is deacetylated and depolymerised to glucosamine salt of the acid used (Figures 1a-c).…”
mentioning
confidence: 99%
“…By an acidic hydrolysis, chitin can be depolymerized and deacetylated to produce GlcN. 17,18 Thus, chitin can be determined from the amount of GlcN residue in the hydrolysate. Usually, HPLC techniques have been employed for the GlcN assay, [19][20][21] although this application presents some difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizopus sp, Mucor sp, Gongronella butleri) [2][3][4][5][6]. GlcN and GlcNAc can also be obtained from the exoskeleton of the crustaceans [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Productions of GlcN using chemical processes are usually carried out by chemical and or enzyme hydrolysis, wherein the energy expenditure leads to increased production cost and also need longer time [7,9]. Several studies have reported the production of GlcN from microbial fermentations.…”
Section: Introductionmentioning
confidence: 99%